Revisiting Ki Hadjar Dewantara’s Among System as a Philosophical Foundation for Early Childhood Education - Asih Rosnaningsih; Ratih Ayu Wulandari; Sholeh Hidayat; Yudi Juniardi (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to examine the core principles of the Among System and to analyze their contextual application in contemporary Early Childhood Education practices. The research employed a qualitative library research design. Data were collected through document analysis of primary sources, including Ki Hadjar Dewantara’s writings, and secondary sources such as scholarly books, peer-reviewed journal articles, and relevant educational literature. The research instrument consisted of document review guidelines focusing on the principles of the Among System and early childhood education concepts. Data analysis was conducted using qualitative content analysis through stages of data reduction, categorization, interpretation, and synthesis. The findings indicate that the principles of Ing Ngarso Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani are conceptually aligned with the nature of early childhood development and contemporary child-centered pedagogical approaches. These principles can be contextualized in classroom interactions, learning facilitation, and formative assessment practices to promote children’s motivation, independence, and agency. In conclusion, Ki Hadjar Dewantara’s Among System remains a relevant and applicable philosophical foundation for enhancing the quality and humanistic orientation of Early Childhood Education.